Natural products in digestive tract tumors metabolism: Functional and application prospects. (May 2023) - Xing, Peng; Zhong, Yifan; Cui, Xiao; Liu, Zhe; Wu, Xingda
Abstract: Digestive tract diseases are presently the hotspot of clinical diagnosis and treatment, and the incidence of digestive tract tumor is increasing annually. Surgery remains the main therapeutic schedule for digestive tract tumor. Though benefits were brought by neoadjuvant chemotherapy, a part of patients lose the chance of surgery because of late detection or inappropriate intervention. Therefore, the treatment of inoperable patients has become an urgent need. At the same time, tumor metabolism is an extremely complex and diverse process. Natural products are confirmed effective to inhibit the development of tumors in vitro and in vitro. There are many kinds of natural products and their functions remain not clear. However, some natural products such as polyphenols have been proven to have definite anti-cancer effects, and some terpenoids have definite anti-inflammatory, anti-ulcer, anti-tumor, and other effects. Therefore, the anti-tumor characteristics of natural products should arouse our high attention. Although there are many obstacles to study the activities of natural products in tumor, including the difficulty in detection or distinguishing each component due to their low levels in tumor tissue, etc., the emergence of highly sensitive and locatable spatial metabolomics make the research and application of natural products a big step forward. In this review, natural products such as phenols, terpenoids and biotinoids were summarized to further discuss the development and therapeutic properties of natural metabolites on digestive tract tumors. Graphical Abstract: ga1